2016
DOI: 10.1016/j.jhep.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

EASL–EASD–EASO Clinical Practice Guidelines for the management of non-alcoholic fatty liver disease

Abstract: DefinitionNAFLD is characterised by excessive hepatic fat accumulation, associated with insulin resistance (IR), and defined by the presence of steatosis in >5% of hepatocytes according to histological analysis or by the proton density fat fraction (PDFF, providing a rough estimation of the volume fraction of fatty material in the liver) >5.6% assessed by proton magnetic resonance spectroscopy ( 1 H-MRS) or quantitative fat/water selective magnetic resonance imaging (MRI). NAFLD includes two pathologically dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
1,920
1
120

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 3,586 publications
(2,057 citation statements)
references
References 150 publications
16
1,920
1
120
Order By: Relevance
“…They found that the AUROC of these biomarkers ranged from 0.80 to 0.88 35. Some of these biomarkers have been suggested by the recent European Association for the Study of the Liver guidelines to assess the severity of fibrosis and rule out advanced stages 23. However, there were no recommendations on any biomarkers to diagnose NASH; liver biopsy remained the only recommendation for this in the recent guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the AUROC of these biomarkers ranged from 0.80 to 0.88 35. Some of these biomarkers have been suggested by the recent European Association for the Study of the Liver guidelines to assess the severity of fibrosis and rule out advanced stages 23. However, there were no recommendations on any biomarkers to diagnose NASH; liver biopsy remained the only recommendation for this in the recent guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies that showed total disagreement among the three pathologists were excluded from the analysis. The histopathologic definition of NASH was determined by the joint presence of steatosis, lobular inflammation, and hepatocellular ballooning on liver specimens, independently of the total NAFLD activity score (NAS) 23. Biopsies with only steatosis, steatosis with inflammation but without ballooning, or steatosis with ballooning but without inflammation were classified as NAFL.…”
Section: Methodsmentioning
confidence: 99%
“…The European Associations for the Study of the Liver (EASL), Diabetes (EASD) and Obesity (EASO) have recently worked together on Clinical Practice Guidelines for the management of NAFLD [7]. According to these guidelines, all individuals with incidentally discovered steatosis should be screened for features of the metabolic syndrome, independently of liver function tests (LFTs).…”
Section: Diagnosis Of Nafld In a Patient With Incidentally Discoveredmentioning
confidence: 99%
“…1), and the screening includes assessment of dietary and lifestyle habits. As regards diet, in addition to total energy intake, particular emphasis should be paid to consumption of simple sugars and saturated fats, both of which are important risk factors for obesity and, independently of obesity for type 2 diabetes, CVD and NAFLD [7,37]. In addition, LFTs, platelets and albumin should be measured to enable calculation of a non-invasive score for NAFLD, such as the NAFLD fibrosis score (based on age, BMI, impaired fasting glucose/diabetes, AST, ALT, platelets, albumin; calculator found at www.…”
Section: Diagnosis Of Nafld In a Patient With Incidentally Discoveredmentioning
confidence: 99%
See 1 more Smart Citation